The Impact of the Bosco Case: An Evolutionary and Critical Analysis of a Ruling that Consolidates Algorithmic Transparency in a Context of Recognition of Social Rights and Vulnerability - Wisner Glusko, Diana Carolina (2025)
The Supreme Court ruling - Spain’s highest court- of September 11, 2025, has compelled the State Administration to grant the CIVIO Citizen Foundation access to the source code of the Bosco software application, designed to verify compliance with the requirements for receiving the social electricity tariff. The decision by the Administrative Chamber of the Supreme Court is itself a turning point in reaffirming the principles of transparency, explainability, auditability, traceability, and accountability when Public Administrations employ automated decision-making systems. In this respect, the ruling itself (Judgment No. 1119/2025), considered a landmark by leading legal scholars, is as important as the path taken by the Foundation and the scope of the decisions adopted at the various administrative and judicial levels. Its significance is even greater given the application of artificial intelligence to the recognition of social rights.The study aims to analyze, in the so-called “Bosco Case” and based on a descriptive, evolutionary and critical analysis, what is the scope of the algorithmic decision and its administrative guarantees when it recognizes a situation of social vulnerability, to what extent the right of access to public information is consolidated when it is algorithmic information and how the configuration of the source code as public information and the necessary balancing of intellectual property before this type of public algorithms have fluctuated, in a Social and Democratic State of Law.